Orders of Social Science: Understanding Social-Scientific Controversies and Confluence on What “High-Quality” Knowledge and “Good” Adaptation Is - Skelton, Maurice (Frontiers in Climate, 2021)
Various scholars have noted—and experienced—tribal tendencies between social-scientific “schools of thought” or “paradigms.” The intensity and fervor of such controversies has led some scientists to compare them with frictions between religious orders. In the research domain focused on the use of climate science for climate adaptation, such disputes revolve around the what “high-quality” climate knowledge and “good” adaptation is or should be. Emphasizing this diversity of orders of social science and the humanities, this article describes five distinct ways social scientists and humanities scholars have thought and written about climate adaptation: descriptivists aim to empirically portray climate adaptation as objectively as possible from an assumed subject-independent perspective; pragmatists' research wants to increase climate resilience through usable climate information; argumentivists strive for assessing the justification of climate scientific findings, as well as adaptation decision-making that is based on these findings; interpretivists seek to empirically redescribe how the use of climate science for adaptation is shaped by, and shapes, various other social processes and political actors; and critical scholars work toward revealing how pervasive powerful interests and marginalizing discourses shape adaptation projects negatively. By comparing these five orders' respective scientific, environmental and social aims and concerns, this article pinpoints to how epistemological, ontological and methodological priorities not only drive scientific controversies on issues such as what “high-quality knowledge” is, but also how interdependent orders' methodological choices are with their epistemological and ontological positions. However, this analysis also reveals that while some scholars implicitly stick to their order, others are comfortable to collaborate across such borders. Overall, the diverging aims, priorities, and methods are unlikely to be ever fully reconciled. A better understanding of why academics from different orders differ in the approaches they take and the issues they care about will likely lead to a larger appreciation of the differences of other orders' research and broaden our understanding of key dynamics in studying “good” climate adaptation and “high-quality” climate knowledge.